PEMANFAATAN TEPUNG UBI JALAR UNGU DAN TEPUNG KELAPA SEBAGAI BAHAN PENSUBSTITUSI TERIGU DALAM PEMBUATAN MI INSTAN - AINIL HIFDA DAULAY; YUSMARINI YUSMARINI; YELMIRA ZALFIATRI (Universitas Riau, 2018)
The purpose of this research was to get the best formulation of purple sweet potato flour and coconut flour inmaking instant noodles. This study was used a completely randomized design experiment with 5 treatmentand 3 replications that produced 15 exsperimental units. The obtained data were statistically analized usinganalysis of variance (ANOVA). If the F count is high than or equal to F table then continued with DNMRT testat the 5% level. The treatments in this research included TUK1 (wheat flour 90: purple sweet potato flour 0:coconut flour 10), TUK2 (wheat flour 85: purple sweet potato flour 5: coconut flour 10), TUK3 (wheat flour 80:purple sweet potato flour 10: coconut flour 10), TUK4 (wheat flour 75: purple sweet potato flour 15: coconutflour 10) and TUK5 (wheat flour 75: purple sweet potato flour 15: coconut flour 10). Result of analiysis ofvariance showed that the ratio of purple sweet potato flour and coconut flour significantly affected moisturecontent, protein content, acid number, intactness, rehydration time and sensory assessment. The best treatmentinstant noodles was TUK4 which had moisture content 4.25%, protein content 10.84%, acid number 1.34 mgKOH/g, intactness 94.67% and rehydration time 6.10 minutes. Descriptive sensory assessment was purplecolour, purple sweet potato flavor, slightly texture and purple sweet potato taste.